PDGF-BB induces expression of LTBP-1 but not TGF-β1 in a rat cirrhotic fat storing cell line - Westhoff, Jens; Sawitza, Iris; Keski-Oja, Jorma; Gressner, Axel M.; Breitkopf-Heinlein, Katja (Growth factors, 2003)
TGF-β, a profibrogenic cytokine is predominantly secreted as a latent molecule complexed with one of the latent TGF-β binding proteins (LTBP). Due to the proposed functions of LTBP-1 and -3 in regulating TGF-β-bioavailability and -activity, we investigated the effects of PDGF-BB and TGF-β1 on their expression levels in Cirrhotic fat storing cells (CFSC). CFSC basally express LTBP-1 and -3 and TGF-β1. LTBP-1 colocalizes with LAP and the cells secrete some active TGF-β1. Promoter studies showed no strong induction of the LTBP-1 promoters after stimulation, although mRNA and protein levels were increased by PDGF-BB treatment without affecting TGF-β1 expression. Vice versa, TGF-β1 treatment did not alter LTBP-1 expression while an autocrine induction was found. Our data indicate that LTBP-1 but not TGF-β1 is induced by PDGF-BB and that TGF-β1 autoinduction does not affect the expression of LTBP-1. This divergent regulation may represent an important mechanism for modulation of TGF-β bioavailability.